3D imaging using cross line laser for box volume estimation - Prayitno, Adhy; Shiddiq, Minarni; Arief, Dodi Sofyan; Dasta, Vicky Vernando; Fitra, Ramma Hayu (AIP conference proceedings, 2020)
Volume measurement is very important for logistics and courier companies in order to be able to estimate shipping cost and space for storage. Machine vision using 3D imaging is potential to be used for box volume measurement. A laser triangulation method can offer simple setup and cost effective system. This study proposes a 3D imaging system using a laser triangulation method for box volume measurement assisted by a cross line laser beam. A Python based algorithms were developed to estimate the width, length, and height from box images, and then the volume of the boxes were calculated. The results were compared to box volumes measured manually. The results show that the system was able to measure width, length, and height using the box images and estimated the box volume with good accuracy. The box volumes range from 1434.5 cm3 to 8245.9 cm3. The difference in the box volumes estimated and measured manually ranges from 0.4 % to 10.2 %. Bigger boxes have higher percentage of difference than smaller size boxes.